Connectivity matters: ultrafast isomerization dynamics of bisazobenzene photoswitches - Slavov, Chavdar; Yang, Chong; Dreuw, Andreas (Physical chemistry, chemical physics, 2016)
We have investigated the ultrafast dynamics of o-, m- and p-bisazobenzenes, which represent elementary building blocks for photoswitchable multiazobenzene nanostructures.
Gesehen am 05.12.2017